The extracellular matrix and mechanotransduction in pulmonary fibrosis. (September 2020) - Deng, Zhenjun; Fear, Mark W.; Suk Choi, Yu; Wood, Fiona M.; Allahham, Amira; Mutsaers, Steven E.; Prêle, Cecilia M.
Abstract: Pulmonary fibrosis is characterised by excessive scarring in the lung which leads to compromised lung function, serious breathing problems and in some diseases, death. It includes several lung disorders with idiopathic pulmonary fibrosis (IPF) the most common and most severe. Pulmonary fibrosis is considered to be perpetuated by aberrant wound healing which leads to fibroblast accumulation, differentiation and activation, and deposition of excessive amounts of extracellular matrix (ECM) components, in particular, collagen. Recent studies have identified the importance of changes in the composition and structure of lung ECM during the development of pulmonary fibrosis and the interaction between ECM and lung cells. There is strong evidence that increased matrix stiffness induces changes in cell function including proliferation, migration, differentiation and activation. Understanding how changes in the ECM microenvironment influence cell behaviour during fibrogenesis, and the mechanisms regulating these changes, will provide insight for developing new treatments.